The Narrative of Identity in the Coverage of Aceh’s Flag - Nurrahmi, Febri (Faculty of Communications Science, Dr. Soetomo University, 2018)
After the governor of Aceh signed the Bylaw no 3/2013 on Aceh’s flag and symbol, the dispute between the local government of Aceh and the government of Indonesia over the adoption of the former separatist group’s flag as the provincial flag erupted. Unlike other studies investigating the way media frame the dispute, the study aims to examine how Serambi Indonesia, the most prominent newspapers in Aceh, used symbolic language in the Aceh’s flag coverage to give meaning to a collective identity within Acehnese society as a flag is regarded as an identity symbol. The sample of news articles was gathered from http://aceh.tribunnews.com within the period from December 2012 to May 2013. The total of 17 news articles was analysed with Gamson and Modigliani’s framing devices. Findings reveal that Serambi Indonesia delivered a conciliatory representation of Acehnese political identity by using flag metaphors, nationalist exemplars, middle ground catchphrases, and ethnocentric depictions.